The peak power problem in OFDM and linearly precoded systems (2005)
In this internship, the peak to average power ratio (PAPR) problem in orthogonal frequency division multiplexing (OFDM) and linear precoding is studied. OFDM is a multicarrier modulation where the siY1al envelope can show high instantaneous peaks due to the addition of modulated symbols. If the siY1al is amplificated by a high power amplifier with non-linear characteristics before transmission, the siY1al peaks may drive the amplifier out of its operation point into saturation. The resultant spectrum may exhibit severe in-band and out-of-band radiation of the distortion components.